2022
DOI: 10.1177/20571585221085989
|View full text |Cite
|
Sign up to set email alerts
|

Methods for involvement of patients, public and users in academic nursing education: A scoping review

Abstract: Involving patients, public and users in health education is currently receiving increased attention. The degree of involvement has changed over time, as have the methods used to involve these groups in nursing education. The purpose of this scoping review was to identify and map available didactic and pedagogical methods for patient, public and user involvement in academic nursing education. Of the initial 9294 articles identified, 21 were included. The PRISMA guideline for scoping reviews was used in the scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Among studies concerning services user and carer participation in health professions' education, mental health is the main practice area reported on (Soon et al, 2020). Within nursing education, such participation appears to be most developed in mental health nursing (O'Donnell & Gormley, 2013; Tørring & Pedersen, 2022). Indicative of this, findings from an Australian survey indicated that 78% of pre‐registration and 75% of post‐registration mental health nursing programmes involved service users and carers (Happell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among studies concerning services user and carer participation in health professions' education, mental health is the main practice area reported on (Soon et al, 2020). Within nursing education, such participation appears to be most developed in mental health nursing (O'Donnell & Gormley, 2013; Tørring & Pedersen, 2022). Indicative of this, findings from an Australian survey indicated that 78% of pre‐registration and 75% of post‐registration mental health nursing programmes involved service users and carers (Happell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%